Higher‐order oligomerization promotes localization of SPOP to liquid nuclear speckles. (24th May 2016) - Marzahn, Melissa R; Marada, Suresh; Lee, Jihun; Nourse, Amanda; Kenrick, Sophia; Zhao, Huaying; Ben‐Nissan, Gili; Kolaitis, Regina‐Maria; Peters, Jennifer L; Pounds, Stanley; Errington, Wesley J; Privé, Gilbert G; et al.
Abstract: Membrane‐less organelles in cells are large, dynamic protein/protein or protein/RNA assemblies that have been reported in some cases to have liquid droplet properties. However, the molecular interactions underlying the recruitment of components are not well understood. Herein, we study how the ability to form higher‐order assemblies influences the recruitment of the speckle‐type POZ protein (SPOP) to nuclear speckles. SPOP, a cullin‐3‐RING ubiquitin ligase (CRL3) substrate adaptor, self‐associates into higher‐order oligomers; that is, the number of monomers in an oligomer is broadly distributed and can be large. While wild‐type SPOP localizes to liquid nuclear speckles, self‐association‐deficient SPOP mutants have a diffuse distribution in the nucleus. SPOP oligomerizes through its BTB and BACK domains. We show that BTB‐mediated SPOP dimers form linear oligomers via BACK domain dimerization, and we determine the concentration‐dependent populations of the resulting oligomeric species. Higher‐order oligomerization of SPOP stimulates CRL3 SPOP ubiquitination efficiency for its physiological substrate Gli3, suggesting that nuclear speckles are hotspots of ubiquitination. Dynamic, higher‐order protein self‐association may be a general mechanism to concentrate functional components in membrane‐less cellular bodies. Synopsis: SPOP, a ubiquitin ligase substrate receptor and tumor suppressor, self‐associates indefinitely into large oligomers via the synergistic function of its tandem dimerization domains. The resulting oligomers are recruited to liquid nuclear speckles, likely generating hotspots of SPOP‐mediated ubiquitination. SPOP localizes to liquid nuclear bodies. Self‐association‐deficient SPOP mutants lose their localization to nuclear speckles. SPOP forms labile higher‐order oligomers through tandem self‐association domains and an isodesmic mechanism. The BTB self‐association‐deficient mutant has a dominant‐negative effect on Hedgehog signaling in the developing fly wing. Dynamic, higher‐order self‐association may be a general mechanism to concentrate functional components in membrane‐less cellular bodies. Abstract : Self‐association of the ubiquitin ligase adaptor and tumor suppressor SPOP is required for its recruitment to liquid nuclear bodies, likely generating hotspots of SPOP‐mediated ubiquitination.